Epidemiological characteristics of human-to-human transmission of severe fever with thrombocytopenia syndrome in China from 1996 to 2023. - Li Yuan; Tingting Tian; Aqian Li; Shanshan Du; Shiwen Wang; Dexin Li; Xiaoxia Huang; Jiandong Li (PLoS Neglected Tropical Diseases, 2025)
Background Severe fever with thrombocytopenia syndrome (SFTS) is an emerging viral disease transmitted mainly through the bite of Haemaphysalis longicornis, and can cause clusters through contact transmission, and its incidence shows a rising and spreading trend in China. This study aimed to analyze the occurrence process of human-to-human transmission clusters and provide evidence for effective implementation of interventions. Methods Data about SFTS human-to-human transmission clusters were extracted from 42 published articles. R 4.4.1 and Microsoft Excel software were used to process and analyze the epidemiological and clinical data extracted. Results 37 clusters occurring from 1996 to 2023 were retrieved, of which 2 (5.41%) involved third-generation transmission, 7 (18.92%) involved 16 asymptomatic infections, and 9 (24.32%) involved 17 medical personnel. There were 37 index cases with a case fatality rate of 97.30%, 135 secondary cases with a case fatality rate of 12.40%, and an overall of 31.33%. The first treatment of the index case was mainly in primary medical institutions (24, 64.86%) and the most common symptoms were fever, fatigue and gastrointestinal symptoms. The index cases were distributed from March to October each year, the peak was from April to July, and the incubation period was 5-21 days, mostly in middle-aged and elderly farmers. Clusters were mainly distributed in Jiangsu Province (9 clusters), followed by Henan, Shandong and Zhejiang Provinces (6 clusters each). The clusters occurred mostly in the progress of care (72.97%), funeral (64.86%) and treatment of patients (24.32%), involving relatives (75.76%), medical workers (12.12%), villagers (9.85%) and morticians (2.27%). Almost all clusters were spread by contact with patients' blood and bloody secretions (97.30%). Conclusions SFTS human-to-human transmission clusters sometimes occur in China, with a high case fatality rate. It is necessary to strengthen public health education, and improve the early diagnosis and treatment ability of medical workers, to avoid nosocomial infection or family (community) transmission.